2000
DOI: 10.1093/emboj/19.11.2615
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the MEF2A-DNA complex: structural basis for the modulation of DNA bending and specificity by MADS-box transcription factors

Abstract: The solution structure of the 33 kDa complex between the dimeric DNA-binding core domain of the transcription factor MEF2A (residues 1±85) and a 20mer DNA oligonucleotide comprising the consensus sequence CTA(A/T) 4 TAG has been solved by NMR. The protein comprises two domains: a MADS-box (residues 1±58) and a MEF2S domain (residues 59± 73). Recognition and speci®city are achieved by interactions between the MADS-box and both the major and minor grooves of the DNA. A number of critical differences in protein±D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(127 citation statements)
references
References 60 publications
6
109
2
Order By: Relevance
“…Indeed, a recent study showed that regions within the C-terminal domain determine functional specificity in AP3 and PI and may be relevant for floral organ evolution (54). The localization of the sites with high PP identified here suggest a role for PDS in MADS-domain protein diversification through interactions with protein partners and changes in affinity to binding motifs (46,47,55). Sites and genes identified here to have been under PDS become interesting targets for functional evaluations.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Indeed, a recent study showed that regions within the C-terminal domain determine functional specificity in AP3 and PI and may be relevant for floral organ evolution (54). The localization of the sites with high PP identified here suggest a role for PDS in MADS-domain protein diversification through interactions with protein partners and changes in affinity to binding motifs (46,47,55). Sites and genes identified here to have been under PDS become interesting targets for functional evaluations.…”
Section: Discussionmentioning
confidence: 70%
“…3). Two of the residues were found within the MADS and correspond to amino acids that in other MADSdomain proteins participate in interactions between subunits (44)(45)(46). For example, site 42 is homologous to a site that in the myocyte enhancer factor-2 has been shown to intervene in subunit folding (45).…”
Section: Mads-box Gene Family Phylogenymentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of a dimer of serum response factor (SRF) to an A͞T-rich site and subsequent recruitment of the ets factor Elk-1 to a GGA core sequence to form a ternary complex (TC) is required for c-fos transcription (11). Both TFs primarily bind DNA in the major groove but make minor groove contacts (12,13). This mode of binding and the presence of an A͞T-rich site make these TFs potential targets for MGTs.…”
mentioning
confidence: 99%
“…2 E and F). Our group has previously shown-via reporter gene assays, chromatin immunoprecipitation (ChIP), and electrophoretic mobility shift assay-that posttranslational redox modification of Cys39 inhibits MEF2 transcriptional activity by interfering with DNA binding (27,28,35,36). Hence, it might be expected that excessive ROS exposure would lead to the formation of SO X H-MEF2D (x = 1-3), thereby impairing transcription of MEF2 target genes.…”
Section: Mef2dmentioning
confidence: 99%